Resistance through inhibition: ectopic expression of serine protease inhibitor offers stress tolerance via delayed senescence in yeast cell - Joshi, Rakesh S.; Tanpure, Rahul S.; Singh, Rajan Kumar; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2014)
Protease inhibitors have been known to confer multiple stress tolerance in transgenic plants. We have assessed growth of yeast (Pichia pastoris GS115) strains expressing inhibitory repeat domains (PpIRD(+)) of previously characterized Capsicum annuum protease inhibitors under high salt, heavy metal and oxidative stress. PpIRD(+) strains exhibited multiple stress tolerance and showed differential molecular responses at transcriptional and translational level on exposure to stress inducing agents like heavy metal, high salt and H2O2. PpIRD(+) strains display significant reduction in metacaspase (Yca1) activity, the key enzyme in apoptosis, indicates the possibility of cross reactivity of IRDs (serine protease inhibitor) with cysteine proteases. PpIRD(+) and Saccharomyces cerevisiae knockout with Yca1 (Delta Yca1) strain showed similar growth characteristics under stress, which indicated the delayed senescence due to cellular metacaspase inhibition. Molecular docking study showed a close proximity of IRDs reactive site and the active site of metacaspase in the complex that signified their strong interactions. Maintenance of GAPDH activity, primary target of metacaspase, in PpIRD(+) strain evidenced the inhibition of metacaspase activity and survival of these cells under stress. This report demonstrates a potential molecular mechanism of protease inhibitor-based multiple stress tolerance in yeast strains. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Metacaspase; Multiple stress tolerance; protease inhibitor; Yeast

Improved tolerance against helicoverpa armigera in transgenic tomato over-expressing multi-domain proteinase inhibitor gene from capsicum annuum - Tanpure, Rahul S.; Barbole, Ranjit S.; Dawkar, Vishal V.; Waichal, Yashashree A.; Joshi, Rakesh S.; Giri, Ashok P.; Gupta, Vidya S. (Physiology and Molecular Biology of Plants, 2017)
Plant proteinase inhibitors (PIs) are plant defense proteins and considered as potential candidates for engineering plant resistances against herbivores. Capsicum annuum proteinase inhibitor (CanPI7) is a multi-domain potato type II inhibitor (Pin-II) containing four inhibitory repeat domains (IRD), which target major classes of digestive enzymes in the gut of Helicoverpa armigera larvae. Stable integration and expression of the transgene in T1 transgenic generation, were confirmed by established molecular techniques. Protein extract of transgenic tomato lines showed increased inhibitory activity against H. armigera gut proteinases, supporting those domains of CanPI7 protein to be effective and active. When T1 generation plants were analyzed, they exhibited antibiosis effect against first instar larvae of H. armigera. Further, larvae fed on transgenic tomato leaves showed delayed growth relative to larvae fed on control plants, but did not change mortality rates significantly. Thus, better crop protection can be achieved in transgenic tomato by overexpression of multi-domain proteinase inhibitor CanPI7 gene against H. armigera larvae.

Nutritional quality and antioxidant activity of wheatgrass (Triticum aestivum) unwrap by proteome profiling and DPPH and FRAP assays - Parit, Santosh B.; Dawkar, Vishal V.; Tanpure, Rahul S.; Pai, Sandeep R.; Chougale, Ashok D. (Journal of Food Science, 2018)
Precious contribution of plants in the field of medicine is very well known. Wheat (Triticum aestivum) seeds and seedlings are an important source of food and feed due to the presence of various health-promoting compounds. Proteomic analysis of three seed developmental stages (0, 8, and 16 days after germination [DAG]) of wheat was carried out using liquid chromatography-mass spectrometry. A total of 297 proteins were identified and their functional annotation revealed that a majority of them were involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy related mechanisms. Particularly to mention, peroxidases, superoxide dismutases, and cytochromes are abundantly present in wheatgrass. In the ferric-reducing antioxidant power assay, antioxidant activity was increased by 1.55 times after 16 DAG as compared to 0 DAG, however it was decreased after 8 DAG. The antioxidant activity of the plant extracts by DPPH had an increasing trend after all the three time points. The percent radical scavenging activity of extract by DPPH was 15, 22, and 30 after 0, 8, and 16 DAG, respectively. Observations obtained revealed that antioxidant power of the plants is directly proportional to the age of seedlings. Data attained on wheatgrass showing that it can be a strong antioxidant agent due to its free radical scavenging activity and could be used in stress and nourishing human health. Practical ApplicationWheatgrass contains minerals, phytochemicals, active enzymes, and vitamins that can be easily absorbed. The consumption of wheatgrass juice can give better health benefits. Information about beneficial properties of wheat grass juice is clearly mentioned in this work.Proteins found in wheatgrass are known to be involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy-related mechanisms. Results of this work revealed that Triticum aestivum seedlings can act as an antioxidant agent due to their free radical scavenging activity and can be constructive to control or treat many health complications. From all these results we believed that wheatgrass can be used for the nourishment of humans.
Keywords: Antioxidant; LC-MSE; peroxidase; proteomics; Triticum aestivum; wheatgrass